French Rococo Ébénisterie in the J. Paul Getty Museum - Desmas, Anne-Lise; Desmas, Anne-Lise; Desmas, Anne-Lise; Desmas, Anne-Lise; Chasen, Jessica; Chasen, Jessica; Heginbotham, Arlen; Heginbotham, Arlen; Wilson, Gillian 1941-2019; Wilson, Gillian 1941-2019 (Book collections on Project MUSE., 2021)
"Catalogue of the Rococo ebenisterie furniture in the collection of the J. Paul Getty Museum"